The Boosters in Boosterism: Some Calgary Examples - Foran, Max (Urban History Review / Revue d'histoire urbaine, 1979)
Through an examination of four Calgary boosters in the pre-1914 period, this article argues that boosterism in the prairie west was largely institutional. The rhetoric of progress was proclaimed loudest in publications produced by business organizations and political bodies. The expansionary policies of prairie cities were pursued by large railway companies or by city councils that were hardly dominated by single individuals. The ethic rather than the individual was dominant and in this respect the latter operated most effectively through representative institutions.